De novo lipogenesis at the mitotic exit is used for nuclear envelope reassembly/expansion : Implications for combined chemotherapy - Rodriguez Sawicki, Luciana (2019)
Mitosis has been traditionally considered a metabolically inactive phase. We have previously shown, however, that extensive alterations in lipids occur as the cells traverse mitosis, including increased de novo fatty acid (FA) and phosphatidylcholine (PtdCho) synthesis and decreased lysophospholipid content. Given the diverse structural and functional properties of these lipids, we sought to study their metabolic fate and their importance for cell cycle completion. Here we show that FA and PtdCho synthesized at the mitotic exit are destined to the nuclear envelope. Importantly, FA and PtdCho synthesis, but not the decrease in lysophospholipid content, are necessary for cell cycle completion beyond G2/M. Moreover, the presence of alternative pathways for PtdCho synthesis renders the cells less sensitive to its inhibition than to the impairment of FA synthesis. FA synthesis, thus, represents a cell cycle-related metabolic vulnerability that could be exploited for combined chemotherapy. We explored the combination of fatty acid synthase (FASN) inhibition with agents that act at different phases of the cell cycle. Our results show that the effect of FASN inhibition may be enhanced under some drug combinations.